INFLUENCE OF MOZZARELLA AND CHEDDAR CHEESE BLENDING ON BAKING PERFORMANCE, VISCOSITY AND MICROSTRUCTURE OF PIZZA CHEESE BLENDS - N. Gulzar1; A. Sameen; S. Rafiq; N. Huma; M. S. Murtaza (Journal of Animal and Plant Sciences, 2020)
Various blends of Mozzarella with 2 and 4 months semi-ripened Cheddar cheese were mixed at levels of 75:25, 50:50 and 25:75 respectively. Effect of different blends of cheeses on baking performance, viscosity and microstructure of pizza cheese were studied. The results showed that L* (whiteness) and -ve a*-values (green color) before and after cooking were significantly (P<0.05) decreased with increasing level and age of Cheddar cheese. The whiteness L* before and after cooking at 75:25 Mozzarella and 2 months semi-ripened Cheddar cheese was (79.45, 83.30) respectively. The values of whiteness before and after cooking at 25:75 Mozzarella and 4 months semi-ripened Cheddar cheese was reduced to 62.41, 79.68 respectively. Viscoelastic behavior showed that “Hot Apparent Viscosity” (HAV) decreased (971.67cP, 655.33cP) while time at 5000 cP viscosity (T5) increased (8.09S, 10.34S) significantly (P<0.05) with increasing proportion and ripening of Cheddar cheese. Microstructure indicated that size of serum channels reduced with higher level and ripening of cheddar cheese. In conclusion baking performance, viscosity and microstructure of Pizza cheese blends are affected by the ripening and blending of fresh and aged cheeses.
Keywords: Viscosity; Micro structure; Pizza cheese blend; Casein; Semi-ripened cheese